Field notes contributed by Lee A. Schoenewe, fall 1996 - Schoenewe, Lee A.et al (1996)
List of birds and locations contributed by Lee A. Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed